2019
DOI: 10.1002/lary.27917
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term evaluation of satisfaction and side effects after modified uvulopalatopharyngoplasty

Abstract: Objectives/Hypothesis: We have previously shown that modified uvulopalatopharyngoplasty (UPPP) is effective to treat obstructive sleep apnea (OSA) and that the effect is stable after 24 months. This continuous report includes questionnaires and phone interviews.Study Design: Prospective intervention study. Methods: Sixty-five patients with apnea-hypopnea index (AHI) score ≥ 15, body mass index <36 kg/m 2 , and Epworth Sleepiness Scale (ESS) score ≥ 8 underwent modified UPPP after failing nonsurgical treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 19 publications
1
8
1
Order By: Relevance
“…In addition, daytime sleepiness, a major symptom of OSA, improved and remained improved in the long term (ESS < 10 in 85% of patients at 8 years post‐UPPP). These beneficial subjective results were also reported in another study of the same cohort, with a high number of satisfied patients (83% at 2 years) 15 …”
Section: Discussionsupporting
confidence: 81%
“…In addition, daytime sleepiness, a major symptom of OSA, improved and remained improved in the long term (ESS < 10 in 85% of patients at 8 years post‐UPPP). These beneficial subjective results were also reported in another study of the same cohort, with a high number of satisfied patients (83% at 2 years) 15 …”
Section: Discussionsupporting
confidence: 81%
“…Swallowing and speech disorders have not been previously well documented after APP in children, but surgical treatment in adults, for example, uvulopalatopharyngoplasty, is known to affect speech and swallowing [23]. In the present study there were no significant differences regarding impaired speech or swallowing, but the study was not powered for these outcomes, and notably, there were three children who reported impaired speech after APP compared to none after ATE.…”
Section: Discussioncontrasting
confidence: 60%
“…Swallowing and speech disorders after APP are not well documented but are well-reported in adults who have received UPPP 151 . While the sample size in Paper III was too small to yield conclusive results, three children reported impaired speech after APP compared to none after ATE.…”
Section: Papers II and Iii -Is Adenopharyngoplasty Better Than Adenotmentioning
confidence: 99%